Karakteristik Klinikohistopatologik dan Profil Imunofluoresensi Kasus Pemfigoid bulosa di Departemen Patologi Anatomik Rumah Sakit Cipto Mangunkusumo Tahun 2011-2018 - Fetisari Kurniawan; Riesye Arisanty (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundBullous pemphigoid is the most common autoimmune bullous disease. It is characterized by the presence of autoantibodies againsthemidesmosomal proteins in dermo-epidermal junction. Immune complexes subsequently induce skin blisters formation clinically, which willappear as subepidermal cleft histopathologically, and revealed as immune depositions immunologically. These three findings are required inorder to estabilsh the diagnosis of Bullous pemphigoid. This study was aimed to asses the clinico histopathological characteristics andimmunofluorescence studies of bullous pemphigoid in Anatomical Pathology Department, Cipto Mangunkusumo General Hospital.MethodsA cross sectional study was conducted in Anatomical Pathology Department ,Cipto Mangunkusumo General Hospital from January 2011 toDecember 2018. Clinical, histopathological, and direct immunofluorescence results were evaluated.ResultsDuring the last 8 years, bullous pemphigoid was the second most common form of autoimmune bullous diseases. The mean age of thesample was 60 years old. Women were affected more common than men (61.6%). Majority of patients present with blisters eruption (67.4%)and most commonly found in the lower extremities (48.8%). Histopathological examinations showed mostly a subepidermal cleft (89.5%)containing infiltrates of eosinophil, neutrophil, and lymphocyte. DIF staining demonstrated 31 cases (36.0%) with immune depositscharacteristic for bullous pemphigoid.ConclusionThe diagnosis of bullous pemphigoid is relied on a combination of clinical, histopathological, and direct immunofluorescence findings.